Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1111/j.1365-2745.2010.01778.x
|View full text |Cite
|
Sign up to set email alerts
|

Abrupt ombrotrophication of a boreal aapa mire triggered by hydrological disturbance in the catchment

Abstract: Summary1. Hydrological changes due to drainage and climate warming can have great impact on the ecosystem balance of boreal mires. The possibility of ombrotrophication, i.e. the development from fen to bog, in response to altered hydrology has not been previously tested. Here, recent changes in vegetation and surface peat are studied in an aapa mire, a typical boreal mire system dominated by fen vegetation. Drainage in the catchment from 1968 onwards led to the change from richly minerogenous to ombrogenous hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(120 citation statements)
references
References 41 publications
6
108
0
1
Order By: Relevance
“…This pattern implies that methanotrophic N 2 fixation contributes to rapid N accumulation in the fen stages. The predicted warming conditions in the northern latitudes (27) may impact on boreal peatland development in two ways: At the southern limit of permafrost, melting is promoting a reverse succession from ombrotrophic bog to fen ecosystem, whereas at the southern border of the fen region (aapamires, wet fen-dominated peatland complexes) drainage due to increased evapotranspiration may accelerate ombrotrophication, i.e., succession toward bog ecosystem (28). Our results indicate that these successional changes are likely to lead to changes in N 2 dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…This pattern implies that methanotrophic N 2 fixation contributes to rapid N accumulation in the fen stages. The predicted warming conditions in the northern latitudes (27) may impact on boreal peatland development in two ways: At the southern limit of permafrost, melting is promoting a reverse succession from ombrotrophic bog to fen ecosystem, whereas at the southern border of the fen region (aapamires, wet fen-dominated peatland complexes) drainage due to increased evapotranspiration may accelerate ombrotrophication, i.e., succession toward bog ecosystem (28). Our results indicate that these successional changes are likely to lead to changes in N 2 dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…If the peat accumulation process continues in a fen, the peat surface will eventually disconnect from the minerotrophic ground water and the fen transforms into a bog. The fen-bog transition (ombrotrophication) has traditionally been described as a unidirectional slow autogenic succession (Zobel 1988), but recent research describes how rapid these shifts may occur (Granath et al 2010, Tahvanainen 2011. For example, Granath et al (2010) showed that the absence of flooding can allow Sphagnum to expand in rich fens, thereby resulting in an ecosystem shift to a poor fen or bog within decades.…”
Section: Introductionmentioning
confidence: 99%
“…Sphagnum mosses are a dominant component of peatlands, a habitat covering more than three percent of the global land area, making up at least half of the world's wetlands, storing one third of the global carbon pool and harbouring many endangered species (Tahvanainen 2011, Loisel et al 2012, Rydin & Jeglum 2013. Two contrasting ecosystems occur within peatlands, dominated either by Sphagnum species or 2015) indicate that both calcium and magnesium are toxic for peatland mosses, but that S. warnstorfii is able to tolerate high levels of magnesium, we determined whether magnesium tolerance coincides with genetic structure at a broad geographical scale.…”
Section: Introductionmentioning
confidence: 99%